Calling for cross-sector engagement with traditional health practitioners in South Africa - Klarmann, Stephanie-Emmy; Kam, Wan; de Waal, Louise Christina (Frontiers in Conservation Science, 2025)
Traditional health practitioners (THPs) are recognised for their roles in maintaining indigenous knowledge and cultural practices, and providing healthcare in local communities, however they have received less recognition as custodians of the environment. Representations of THPs being responsible for wildlife losses has resulted in perceptions that the traditional health and conservation sectors are working in opposition. We argue that THPS are underrepresented in environmental governance and need to be included in conservation decision-making. A two-day workshop with South African THPs was held to explore the role THPs can play in wildlife conservation and reducing wildlife consumption. Our findings highlighted THPs’ roles in communities, misconceptions hindering trust and collaboration with the conservation sector, the importance THPs place on biodiversity and environmental protection. Workshop attendees wanted greater communication and collaboration between THPs, conservationists, and decision makers; and to be recognised as environmental custodians and rectify misconceptions regarding wildlife product usage. In this short communication we aim to open important dialogues between the THPs and the conservation sector in South Africa and advocate for a more collaborative way forward in conservation decision making.